PENGARUH EDUKASI KESEHATAN MELALUI MEDIA VIDEO ANIMASI BERBASIS DORATOON TENTANG POLA DIIT DM TERHADAP PENGETAHUAN PASIEN DIABETES MELITUS - Mudzakkir, Muhammad; Prihananto, Dhian Ika; Fatah, Nawaris Sufil (Universitas Pesantren Tinggi Darul Ulum, 2023)
Diabetes mellitus (DM) is an endocrine disorder characterized by instability of blood glucose levels. One of the important factors that can regulate blood sugar levels is regulating dietary patterns, so patient understanding regarding management is needed. Education as one of the pillars of management of DM patients plays an important role as a means of promoting holistic DM management. This research aims to determine the effect of health education through Doratoon-based animated video media about DM diet patterns on the knowledge of diabetes mellitus patients. The research design uses a quasi experiment with a one group pre and post test design without control group. The sample used was 30 DM patients with a purposive sampling technique. The research instrument is a questionnaire regarding knowledge of DM diet patterns. The data obtained were analyzed using Wilcoxon. The result obtained was a value of p = 0.001 (p<0.05) which shows that there is an influence of providing health education through Doratoon-based animated video media about DM diet patterns on the knowledge of diabetes mellitus patients. Future researchers are expected to be able to develop digital media in various forms of animation for health education. Keywords: Health Education, Animation videos, Knowledge, Diet Patterns, Diabetes Mellitus.